Driving factors of digital strategic actions in competitive dynamics. (14th June 2019) - Hu, LeWei; Zhao, Jing; Huang, Jiao; Li, Yajing
Based on the competitive dynamics theory and from the exploitation/exploration perspective, this study explored the impetus and differences in incremental and radical digital strategic actions (DSAs) using 250 cases. We found that the quantity and diversity of partners were the core factors for launching successful incremental DSAs, and partnership strength was the core condition to start successful radical DSAs. We also found that digital assets' depth and breadth was the necessary prerequisites to initiate the two types of DSAs. This study aimed to help managers formulate and initiate competitive actions more effectively in a digital environment.